Adolescent experiences and adult work outcomes - Greve, Henrich R.; Seidel, Marc-David L. (Bingley, U.K. : Emerald, 2014)
This volume of Research in the Sociology of Work starts with a deceptively simple question of, "Do events and experiences during adolescence influence the work outcomes of individuals when they reach adulthood?" While at first glance simple, the question has a wide range of theoretical and practical implications, which are covered in a compelling set of contributions. The volume contains new and exploratory research related to this fundamental question and highlights the opportunities for further research on the topic.
Adolescent experiences and adult work outcomes : connections and causes / Henrich R. Greve, Marc-David L. Seidel -- In search of the self at work : young adults' experiences of a dual identity organization / Michel Anteby, Amy Wrzesniewski -- Adolescent socialization and the development of adult work orientations / Kathryn H. Dekas, Wayne E. Baker -- What you value or what you know? Which mechanism explains the intergenerational transmission of business ownership expectations? / Jason Greenberg -- The long arm of the life course : adolescent experiences and the evaluation of job security in early adulthood / Jack Lam -- Sex, drugs, and rolling rocks : adolescent counter-normative behaviors and their job mobility as young adults / Henrich R. Greve -- Beneficial "child labor" : the impact of adolescent work on future professional outcomes / Marjan Houshmand, Marc-David L. Seidel, Dennis G. Ma -- Going for the gold : the effect of competitive socialization on managerial attainment / Sharon Koppman.
Includes indexes.
Print version record
Keywords: Social Science -- Children's Studies; Sociology: work & labour; Young adults -- Employment; Young adults -- Economic conditions